(untitled) (Global Journal of Human-Social Science, 2024)
Kerbside collection of waste is not often included as part of carbon footprint analysis in view that it constitutes about 5e percent of the carbon emissions generated by the waste collection and treatment systems. However, it also represents the most expensive functional element in the entire waste management process, reaching as high as 75 percent of all costs in the total municipal solid waste (MSW) management system. Most costs relate to fuel, together with labour costs. Fuel consumption results in various pollutants, predominantly carbon dioxide, nitrogen oxides and sulfur dioxide, which are of major concern due to their contribution to global warming and acid rain. In Malta, transport emissions generated from the MSW collection system reach 14 percent of total emissions. This is significantly higher than the European average which generally reaches 5 percent. During the time the study was carried out, the local councils (municipalities) were left to their own devices to sketch a collection route with the result that truck drivers often outline a route simply on their experience.